PROFIL TINGKAT PEMAHAMAN SISWA SMP KELAS 7 PADA MATERI PEMANASAN GLOBAL - Rahayu, Hani Nursuci; Latip, Abdul; Rahmaniar, Andinisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the level of understanding of the concept of global warming among 7th-grade junior high school students in Garut Regency. The method used is a one-shot case study with an instrument in the form of a global warming comprehension test. The research subjects consisted of 31 students who had received relevant material in their learning. Data analysis results showed that no students had a high level of understanding (0%), 13 students were in the medium understanding category (44%), and 18 students were in the low understanding category (54%). These results indicate that the majority of students still have a low understanding of the concept of global warming. This low comprehension is likely due to less interactive teaching methods and limited learning resources. Therefore, more innovative learning strategies, such as the use of interactive media and project-based approaches, are needed to enhance students' understanding of this environmental issue